2017
DOI: 10.1016/j.coi.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Peptide vaccines in cancer — old concept revisited

Abstract: Synthetic peptide vaccines aim to elicit and expand tumor-specific T cells capable of controlling or eradicating the tumor. Despite the high expectations based on preclinical studies, the results of clinical trials using peptide vaccines have been disappointing. Thus, many researchers in the field have considered peptide vaccines as outdated and no longer viable for cancer therapy. However, recent progress in understanding the critical roles of immune adjuvants, modes of vaccine administration and T cell dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 69 publications
0
68
0
2
Order By: Relevance
“…Since the discovery of cancer‐related antigens in the 1990s, cancer immunotherapy has developed as a promising cancer treatment based on cancer‐specific activation of the host immune system . To date, many basic studies and clinical trials of cancer peptide vaccines and adoptive T cell therapies have been conducted for the treatment of cancer patients . However, while some trials have reported clinical efficacy, cancer vaccine therapies are not yet a standard therapy for cancer patients.…”
mentioning
confidence: 99%
“…Since the discovery of cancer‐related antigens in the 1990s, cancer immunotherapy has developed as a promising cancer treatment based on cancer‐specific activation of the host immune system . To date, many basic studies and clinical trials of cancer peptide vaccines and adoptive T cell therapies have been conducted for the treatment of cancer patients . However, while some trials have reported clinical efficacy, cancer vaccine therapies are not yet a standard therapy for cancer patients.…”
mentioning
confidence: 99%
“…Peptide Vaccines So far, peptide vaccines aim to elicit and expand tumor-specific T cells capable to control or eradicate the tumor and may be more efficacious in patients with minimal residual disease than in patients with broadly disseminated metastatic disease [24]. Despite the high expectation based on preclinical studies, the results of preliminary studies using peptide vaccines have been disappointing.…”
Section: Other Immune Strategiesmentioning
confidence: 95%
“…as assessed in Gros et al 2016; Linnemann et al 2015; McGranahan et al 2016; Pritchard et al 2015a; Robbins et al 2013; Schmidt et al 2017; Snyder et al 2014; van Rooij et al 2013). The possible reasons behind suboptimal immunogenicity of peptide vaccines for cancer are reviewed by Kumai et al (2017). …”
Section: Identification Of Neoantigensmentioning
confidence: 99%